Mainstreaming biodiversity for food and nutrition into policies and practice: methodologies and lessons learned from four countries - Beltrame, Daniela M.O.; Gee, E.; Guner, B.; Lauridsen, Nina Olsen; Samarasinghe, W.L.G.; Wasike, Victor W.; Hunter, D.; Borelli, Teresa (Anadolu Ege Tarimsal Arastirmalar Enstitusu Dergisi, 2019)
This paper outlines the methodology for mainstreaming biodiversity developed by the Biodiversity for Food and Nutrition Project (BFN), a multi-country initiative led by Brazil, Kenya, Sri Lanka and Turkey. BFN explored the nutritional properties of traditional and/or neglected native edible species, both wild and cultivated (including varieties and landraces), and used this knowledge to incorporate local agricultural biodiversity into national and global policy instruments that address food and nutrition security through the promotion of healthy, diversified and sustainable diets. Across the four countries, the project adopted a three-pillar approach for mainstreaming biodiversity for food and nutrition into policies and practices by: 1) Providing Evidence, 2) Influencing Policy, and 3) Raising Awareness. Case study examples from Brazil, Kenya, Turkey, and Sri Lanka demonstrate how the approach can be adapted to suit specific country contexts and how a multi-level, cross-sectoral partnership-based approach can create an enabling environment for mainstreaming biodiversity to improve nutrition.